Nas teias de justiça: a justiça régia em Goiás no século XVIII - Acevedo, Jefferson Roberto Nascimento (2019)
This paper aims to make an exposition about the problems between the operation of the justice network in Goiás and its links with Portugal. In order to question the discourse of neutrality and justification of the positive order and its emergence in the codification of the Roman law to ordinations. The administration of justice will be one of the priorities of the Portuguese government, once again, it also guarantees the full functioning of the empire. The bureaucracy will be installed in the colonies in order to fulfill the monarch’s will and at the same time achieve ascension through the mercies and privileges of those who serve the Crown, a relation which presents itself in a dubious way, while apparently serving the will of ELRey, which are pursuing their own interests. Thus, the monarch brings close to himself a toga nobility who, from law and academic knowledge, will contribute to the functioning of the administration and the justification of royal power. Brazil in the 18th century is of a great importance of understanding the operation of the administration of justice, due to the complexity that is established after the creation of two courts, the Bahia and Rio de Janeiro. In this context, Goiás, which is apparently separated from all these convulsions of events, participates in a justice network, logically with its peculiarities.